Strategy for developing da'wah broadcast programs on television in the millennial era - Ahmad Zaini; Nur Ahmad (Jurnal Ilmu Dakwah, 2022)
Purpose - This study aims to determine the planning and production of religious broadcast programs and to find strategies for developing Da'wah broadcast programs so that millennials are interested.Method - This study uses a qualitative method. Data collection techniques use the methods of observation, interviews, and documentation.Result - The contribution of this research is about the importance of the strategy of developing da'wah through television in order to present popular, and competent sources without any hidden agenda, and have different backgrounds. In addition, cadre presenters from the millennial generation, generation Z, empowered presenters who are eye-catching, fashionable, smart, communicative, capable of public speaking, smart in their way of thinking, and influencers who have lots of followers.Implication - The contribution of this research is about the importance of the strategy of developing da'wah through television in order to present popular and competent sources without any hidden agenda, and have different backgrounds. In addition, cadre presenters from the millennial generation, generation Z, empowered presenters who are eye-catching, fashionable, smart, communicative, capable of public speaking, smart in their way of thinking, and influencers who have lots of followers.Originality - This study focuses on the development of da'wah through television so that it continues to exist in this millennial era.***Tujuan - Penelitian ini bertujuan untuk mengetahui perencanaan dan produksi program siaran religi serta menemukan strategi pengembangan program siaran dakwah agar diminati generasi milenial.Metode – Penelitian ini menggunakan metode kualitatif. Teknik pengumpulan data menggunakan metode observasi, wawancara, dan dokumentasi.Hasil - Kontribusi penelitian ini adalah tentang pentingnya strategi pengembangan dakwah melalui televisi agar menghadirkan narasumber yang populer, kompeten, tanpa agenda tersembunyi, dan memiliki latar belakang yang berbeda. Selain itu, kader presenter dari generasi milenial, generasi Z, presenter berdaya yang eye-catching, fashionable, smart, komunikatif, mampu public speaking, cerdas cara berpikirnya, dan influencer yang memiliki banyak followers.Implikasi - Kontribusi penelitian ini adalah tentang pentingnya strategi pengembangan dakwah melalui televisi untuk menghadirkan narasumber yang populer dan kompeten tanpa agenda tersembunyi, serta memiliki latar belakang yang berbeda. Selain itu, kader presenter dari generasi milenial, generasi Z, presenter berdaya yang eye-catching, fashionable, smart, komunikatif, mampu public speaking, cerdas cara berpikirnya, dan influencer yang memiliki banyak followers.Orisinalitas - Kajian ini berfokus pada perkembangan dakwah melalui televisi agar tetap eksis di era milenial ini.